A green supplier selection framework in polyethylene industry - Asgharnezhad, Arezou; Avakh Darestani, Soroush (Emerald, 2021)
To outsource part of their work, organizations are looking for suppliers who also have green criteria with other criteria. Selecting suppliers begins with the definition of potential suppliers and then selects the best among them. In this work, a two-part approach for selecting suppliers consisting of suppliers’ prioritization is presented. In the first part, the criteria that influence on selecting the suppliers have been identified and extracted using the literature review and experts’ opinion which consists of 19 criteria. Then, these criteria were evaluated by the CVR index and using experts' opinions, and finally 16 criteria were selected for selecting green suppliers in a polyethylene’s products producer company in Iran. In the next step, suppliers are selected in a green supply chain using multi-criteria decision making methods such as Dempster-Shafer theory and gray relationship analysis, which is a strategic decision. This study attempts to improve the level of reliance on the whole uncertain degree by combining Dempster-Shafer theory and grey relational analysis, which makes the grey analysis method more robust and its results more reliable.